The Association Between Leaf Malondialdehyde and Lignin Content and Resistance to Spot Blotch in Wheat. Issue 11 (8th August 2016) - Yusuf, Comfort S.; Chand, Ramesh; Mishra, Vinod K.; Joshi, Arun K.
Abstract: Spot blotch (causative pathogen Bipolaris sorokiniana (Sacc.) Shoem) is a common disease of wheat in the Eastern Gangetic Plains region of India. The association of leaf malondialdehyde and lignin contents with the severity of spot blotch disease was studied using a correlation analysis based on a population of recombinant inbred lines bred from the cross cvs. Yangmai 6 (resistant) × Sonalika (susceptible). The material was field‐tested over two consecutive years and inoculated artificially with a highly virulent strain of the pathogen. Disease severity was assessed at three growth stages around and after anthesis. Leaf lignin content tended to be higher in the more resistant RILs, while the opposite was the case for leaf malondialdehyde content. Lesion size showed a positive correlation with disease severity and leaf malondialdehyde content, while disease severity and leaf lignin content were negatively correlated with one another, as were leaf malondialdehyde and leaf lignin content. Leaf malondialdehyde and/or leaf lignin content could be informative as markers for selection for higher levels of resistance against spot blotch in wheat.